2017
DOI: 10.1056/nejmoa1610493
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Hypothermia after In-Hospital Cardiac Arrest in Children

Abstract: BACKGROUND-Targeted temperature management is recommended for comatose adults and children after out-of-hospital cardiac arrest; however, data on temperature management after inhospital cardiac arrest are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
255
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(268 citation statements)
references
References 39 publications
(46 reference statements)
6
255
0
5
Order By: Relevance
“…In 2017, the long-awaited results of the therapeutic hypothermia after in-hospital cardiac arrest were published [18]. Similar to the previously reported out-of-hospital THAPCA trial, there was no benefit for moderate hypothermia compared to controlled normothermia on survival with a good neurobehavioral outcome.…”
Section: Post-icu Survivor Outcomesmentioning
confidence: 55%
“…In 2017, the long-awaited results of the therapeutic hypothermia after in-hospital cardiac arrest were published [18]. Similar to the previously reported out-of-hospital THAPCA trial, there was no benefit for moderate hypothermia compared to controlled normothermia on survival with a good neurobehavioral outcome.…”
Section: Post-icu Survivor Outcomesmentioning
confidence: 55%
“…However, for IHCA, hospital response times in initiating cardiopulmonary resuscitation are likely more rapid than from bystanders during OHCA, the advantages of initiatingTTM treatment in the In-Hospital setting to reduce reperfusion injury due to prolonged brain anoxia may differ as compared with the Out-of-Hospital setting. To date, randomized trials of TTM for IHCA in adults do not exist but a recent trial of TTM in children for IHCA found no difference in In-Hospital and 1 year survival between those managed with TTM to 32 to 34 Celsius vs. a control group which focused on avoidance for fever [15]. Additionally, observational studies, though limited, have not found a consistent benefit of TTM for patients with IHCA.…”
Section: Discussionmentioning
confidence: 99%
“…This generated a list of clinical trials and review articles, including a recent multicenter randomized control trial addressing the topic of therapeutic hypothermia for in-hospital cardiac arrest in pediatric patients. 1 Using the bibliography for this trial, two retrospective studies addressing the same topic were identified. 2 Additionally, a multicenter randomized control trial addressing out-of-hospital cardiac arrest in pediatric patients was identified.…”
Section: Related Literaturementioning
confidence: 99%